Highly-Skilled Migrants, gender, and well-being in the Eindhoven region: An intersectional analysis - Camilla Spadavecchia; Jie Yu (Administrative Sciences, 2021)
The shortage of skilled labor and the global competition for highly qualified employees has challenged Dutch companies to develop strategies to attract Highly Skilled Migrants (HSMs). This paper presents a study exploring how well-being is experienced by HSMs living in the Eindhoven region, a critical Dutch Tech Hub. Our population includes highly skilled women and men who moved to Eindhoven for work or to follow their partner trajectory. By analyzing data according to these four groups, we detect significant differences among HSMs. Given the exploratory nature of this work, we use a qualitative method based on semi-structured interviews. Our findings show that gender plays a crucial role in experienced well-being for almost every dimension analyzed. Using an intersectional approach, we challenge previous models of well-being, and we detect different factors that influence the respondents' well-being when intersecting with gender. Those factors are migratory status, the reason to migrate, parenthood, and origin (EU/non-EU). When all the factors intersect, participants' well-being decreases in several areas: career, financial satisfaction, subjective well-being, and social relationships. Significant gender differences are also found in migration strategies. Finally, we contribute to debates about skilled migration and well-being by including an intersectional perspective.
Keywords: 350; Eindhoven; gender; Highly Skilled Migrants; intersectionality; The Netherlands; well-being